Genome-wide identification, immune response profile and functional characterization of IL-10 from spotted knifejaw (Oplegnathus punctatus) during host defense against bacterial and viral infection - Wang, Jie; Chen, Zhangfan; Li, Ming; Ziwei zhang; Song, Yu; Xu, Wenteng; Wang, Lei; Chen, Songlin (Fish & shellfish immunology, 2022)
Interleukin 10 (IL-10), a pleiotropic cytokine, plays an essential role in multiple immunity responses. In the current study, the sequences of IL-10 family were identified from spotted knifejaw (Oplegnathus punctatus) whole genome, and O. punctatus IL-10 (OpIL-10) was cloned and characterized. OpIL-10 encodes 187 amino acids with a typical IL-10 family signature motif and predicted α-helices. It shared high identities with Notolabrus celidotus IL-10 and Epinephelus Lanceolatus IL-10. OpIL-10 was widely detected in healthy tissues, with the abundant expression in liver and skin. It was significantly up-regulated in the six immune-related tissues (liver, spleen, kidney, intestine, gill and skin) after infection against Vibrio harveyi and spotted knifejaw iridovirus (SKIV). Dual-luciferase analysis showed that OpIL-10 overexpression could suppress the activity of NF-κB. Meanwhile, OpIL-10 knockdown caused the down-regulation of five immune-related genes in JAK2/STAT3 signaling pathway and NF-κB signaling pathway, including IL-10R2, TYK2, STAT3, NOD2, and IκB. In addition, LPS and poly I:C stimulated expression of pro-inflammatory cytokines, including IL-6, IL-1β, IL-8, and IL-12, were lower with recombinant OpIL-10 (rOp IL-10) than the control group, indicating the anti-inflammatory roles of rOpIL-10. Taken together, these results indicated OpIL-10 as a negative regulator in the inflammatory responses of spotted knifejaw against bacterial and viral infection, which would help us better understand the role of IL-10 in teleost immunity. •OpIL-10 was identified and characterized from spotted knifejaw (Oplegnathus punctatus).•OpIL-10 was expressed in multiple tissues and upregulated in six immune-related tissues after bacterial and viral infection.•OpIL-10 could regulate JAK2/STAT3 signaling pathway and NF-κB signaling pathway.•Recombinant OpIL-10 protein had an inhibitory effect on the expression of proinflammatory cytokines.•OpIL-10 plays a negatively regulator in the immune response against bacterial and viral infection in spotted knifejaw.